Effective Use of Online Tools to Prepare Students for Competitive Examinations - Lokare, Varsha T.; Shingan, Gautami; Jadhav, Prakash; Dharwadkar, N. V. (Journal of Engineering Education Transformations, 2020)
To prepare students for various competitive examinations like GATE, GRE etc it is a challenging task as it requires basic understanding of the courses. Also it needs lots of practice to solve complex problems. So, in this paper the use of three online tools: Gate Test series, Answer Garden and Polls Everywhere is been described for the course operating system. As Operating System course has higher weight-age in various competitive examinations like GATE. So, we choose this course as a case study to apply online tools. Finally the comparative analysis has been done for MCQ-Test1 marks where these tools were not used and MCQ-Test2 which was conducted after applying these tools